Snf1-related kinase improves cardiac mitochondrial efficiency and decreases mitochondrial uncoupling - Amy K. Rines (Nature Portfolio, 2017)
The Snf1-related kinase (SNRK) is widely expressed and yet its function is poorly understood. Here the authors show that SNRK regulates mitochondrial coupling via the Trib3-PPARα-UCP3 pathway and that cardiac overexpression of SNRK decreases metabolic substrate usage and oxygen consumption but maintains cardiac function and energy in mice.